Prototype SmartHome Lampu dan Kipas Otomatis Menggunakan Sensor Cahaya LDR dan Suhu Berbasis NodeMCU Esp8266 dengan Kendali Telegram - Sewaka; Maehcel Rahman (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
The widespread use of the Internet has given birth to a new concept called the Internet Of Things (IoT). This concept is based on expanding the use and benefits of the Internet by embedding a controller and sensors that can connect and share data continuously. Therefore, there is a prototype Smart Home system that can control automatic lights, and automatic fans with access control using the Telegram application. Using LDR and DHT22 sensors are sensors used in this tool with a microcontroller, namely NodeMCU ESP-8266. LED sensor detects a light intensity value of less than 600. The fan is the output result of the DHT22 sensor when the sensor detects a temperature of more than 33o Celsius. The data obtained from the sensor will be received and sent to the NodeMCU for later to be displayed on the telegram application as a form of monitoring and the user can control it through the telegram application.